THE IMPORTANCE OF THE FINANCIAL MARKET IN THE ECONOMY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study analyzes the role and importance of the financial market in the economy. The financial market plays an important role in the concentration of capital, efficient allocation of resources, stimulation of investments and ensuring economic growth. The study examines the main functions, structure and impact of the financial market on economic processes. The efficiency, transparency and stability of the financial market are assessed as important factors of economic development. The study also analyzes policies for the regulation, control and development of the financial market. In conclusion, it is emphasized that the financial market is an integral part of the economy and its stable functioning is necessary for ensuring economic growth and prosperity.